Detection of Central Nervous System Infiltration by Myeloid and Lymphoid Hematologic Neoplasms Using Flow Cytometry Analysis: Diagnostic Accuracy Study - Bento, Laiz Cameirão; Correia, Rodolfo Patussi; Alexandre, Anderson Marega; Nosawa, Sonia Tsukasa; Pedro, Eduardo de Carvalho; Vaz, Andressa da Costa; Schimidell, Daniela; Fernandes, Gustavo Bruniera Peres; Duarte, Carlos Augusto Senne; Barroso, Rodrigo de Souza; Bacal, Nydia Strachman (Frontiers in Medicine, 2018)
Introduction: Infiltration of the central nervous system by hematologic or lymphoid malignant cells can cause extensive neurological damage, be progressive and fatal. However, usually, the cerebrospinal fluid (CSF) has low cellularity and rapid cell degeneration, which can impair cytometry analysis. Storage and transport measures, sample preparation and staining protocols can interfere with diagnostic accuracy. Objective: To calculate the diagnostic performance of flow cytometry using a cell stabilizer for sample preservation compared to cytomorphology in the detection of central nervous system infiltration by lymphoid and hematologic neoplasms. Methods: Cell samples from all consecutive patients with suspected infiltration by hematological malignancies evaluated between January 2014 and December 2016 were included. Cases were analyzed by flow cytometry using a cell preservation medium and cytomorphology. Sensitivity and specificity were calculated. Results: From 414 CSF samples, 72 had a phenotype compatible with characteristics of infiltration by hematological disease, whereas cytology was positive for 35 cases. Flow cytometry showed higher sensitivity and specificity when compared to cytomorphology, particularly in cases with cellularity under 5 leukocytes/mm3. Conclusion: We demonstrated that collecting cerebrospinal fluid in a medium that preserves the stability of the sample improves accuracy when compared to cytomorphology, particularly in low-volume and low-cellularity samples.